KEBIJAKAN PERLINDUNGAN PEKERJA ANAK (Kasus Pekerja Anak yang Terperangkap Dalam Bentuk-Bentuk Pekerjaan Terburuk di Kota Surakarta) (JIANA ( Jurnal Ilmu Administrasi Negara ), 2013)
Policies on the protection of child labor has been createdand implemented by the government, but cases of child labor issues always arise. This study aims todetermine the profile of child labor, the factors that lie behind them, and an alternative implementationof child labor protection policy. By the survey design, data were collected through questionnaireinstruments, in-depth interviews, and observation. The population was children trapped in theintolerable forms of child labor. The sampling technique used was purposive sampling with a sample of45 child labor. Data were analyzed using descriptive statistical analysis , and categorization analysis.The results showed that in general, children are not school workers, male sex, having work between 4-8hours per day, with an average income of Rp 25.000,- per day. The background conditions they work isbecause the economic conditions are worse, some have experienced sexual violence, and are victims ofsexual trafficking. In addition, the implementation of child protection policies have not been effectivedue to problems concerning child labor parties and is multidimensional.Keywords: policy implementation, child labor, intolerable forms of child labor, sexual violence, sexualtrafficking.